Analysis of Product Differentiation Strategy to Obtain Competitive Advantage in MSMEs - Jayadi, Mhd Dimas; Hayati, Fitri; Atika, Atika (Image : Jurnal Riset Manajemen, 2023)
Tight business competition occurs in various fields, including the beverage industry, so that business actors need to create competitive advantages by implementing differentiation strategies so that companies have an identity or characteristic of the products they produce. Warung TST Mas Jay must implement a differentiation strategy in order to gain an advantage in the competition. This study examines the differentiation strategy to create competitive advantages in Warung TST Mas Jay, the purpose of the study is to determine the application of differentiation strategies to create competitive advantages in Warung TST Mas Jay. The research method used is a qualitative approach with a qualitative descriptive research type. Business competition is carried out in accordance with Islamic teachings, namely competing healthily and not harming other parties. Warung TST Mas Jay implements product differentiation strategies to create competitive advantages.